Content marketing effect on customer retention: Using customer engagement as intervening variable - Wynne Martivia; Awisal Fasyni (Marketing Management Studies, 2022)
The goal of this study is to investigate how content marketing, an intervening variable, affects customer engagement and retention at Instagram Coffee Shop Chakovi in Padang City. 200 people who had visited a Chakovi coffee shop in Padang and had viewed Instagram posts as well as made purchases made up the sample for this study. Purposive sampling is the sampling method. SEM analysis was used to analyze this research using SmartPLS software 3.3.9. (1) Content marketing has a favorable and considerable impact on customer retention, according to this study's findings. (2) Customer Engagement is positively and significantly impacted by content marketing. (3) Customer Retention is positively and significantly impacted by customer engagement. (4) Customer Retention is positively and significantly impacted by content marketing due to increased customer engagement.